Screening and Triage Cubicle (S.A.T.CUBE) design for COVID-19 - Mhd Zain, Mhd Hafiz Karami; Wan Ismail, Wan Azlina; Md Alwi, Najah; Mohd Nawawi, Norwina; Wan Ibrahim, Wan Fauzi; Ismail, Azirawati; Mohd Zubir, Mohd Zurairie (2021)
Corona Virus Disease 2019 (COVID-19) pandemic occurred worldwide in 2020 until now has intensified global healthcare institutions to execute screening methods to identify the virus, along with means to contain the spread. Therefore, the healthcare personnel especially doctors and nurses who involve in COVID-19 screening have an increased risk of exposure to this virus every day. However, the combination of local climate, paired with extended hours working in personal protective equipment (PPE) suits, has resulted in extensive mental and physical exhaustion reported among health workers. In addition, the hospitals were also facing other issues with medical supplies shortage in the personnel protective equipment (PPE)suits. Thus, this innovation is an idea borne out of a need to assist and provide safe and convenient space for healthcare personnel during the screening and triage phase for COVID-19 suspected patients. By combining inputs from experts in the medical field, medical space planners and architecture experts, we came out with a design of a Screening and Triage Cubicle (S.A.TCube) which provide safer space for medical personnel by having safe platform and isolation between doctor without any complicated structure and expensive mechanical ventilation. In addition, health personnel can conduct COVID-19 screening activities without wearing a PPE suit. In conclusion, the S.A.T Cube is still in its early design phase and is planned for further development toward a buildable prototype. The potential of this product design lies in its purpose to alleviate the physical burden of donning long hours of PPE suits which health workers when a larger quantity of COVID19 screenings take place. Subsequently, the cube can also be commercialised for further custom design features that would be of use to interested institutional parties.